Evaluasi Penerapan STCW Amandemen 2010 di Sekolah Pelayaran di Semarang - Susanto Susanto; Ngatmin Ngatmin; Nanang Indradi (Jurnal Maritim Polimarin, 2019)
The International Convention on Training. Certification and Watchkeeping Standards for Seafarers 1978 (STCW1978), as amended in 1995 and last amended in 2010 the Manila Amendment 2010was intended to implement all changes agreed upon at STCW-95 by incorporating new technology. The time given by IMO to implement the 2010 STCW amendment convention to all its members in implementing changes is 5 years ending on January 1, 2017. This affects the institutions that provide education and training are required to be able to fulfill all changes and requirements. Shipping schools in Indonesia are required to apply the Minister of Transportation Regulation Number PM 70 of 2013 concerning Education and Training, Certification and the Guarding Service of Seafarers. The research method used is Indepth Interview or in-depth interviews with the population and samples are schools and shipping academies in the city of Semarang. Interviews were used to explore data related to the implementation of the 2010 STCWamendment rules in the schools concerned. The research data obtained are in the form of interviews written. The results of the interviews were then analyzed by understanding the relationship between the questions with each other by comparing the technical rules for the implementation of education and training for seafarers. The results of the study on the evaluation of the implementation of the 2010 amendment STCWas outlined in reference to the Minister of Transportation Regulation Number PM 70of 2013 obtained several conclusions. Shipping schools have difficulty meeting facilities including simulators. The biggest difficulty faced is funding because the price of simulators is quite expensive and the instructors are competent with seafarers. The role of the government is still very lacking in providing support and assistance in meeting the requirements that must exist for the smooth process of education.